Wet and dry cooling affect the postharvest life of cut flowers of Lisianthus (Eustoma grandiflorum) ‘ABC Blue Rim’ - Pérez-Arias, Gloria Alicia; Alia-Tejacal, Irán; Valdez-Aguilar, Luis Alonso; Colinas-León, María Teresa; López-Martínez, Víctor; Sainz-Aispuro, Manuel de Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
Vase-life was evaluated in lisianthus inflorescences ‘ABC Blue Rim’ stored wet or dry for 5, 10 and 15 days at 3 °C and 85% relative humidity (RH) in darkness; before storage, a solution at 3% of sucrose + 200 mg L-1 of Hydroxyquinoline citrate for 24 h was applied. Leaving low temperature, vaselife was evaluated in a chamber with a temperature of 20 ± 1 °C and 80 ± 2% RH, during 12 h light/dark and PAR of 173 ± 50 µmol m2s-1. A group of inflorescences was stored at low temperature (control); these inflorescences showed climacteric, a relative increased fresh weight (7.2%), water consumption (31.1 mL stem-1) and stomatal conductance (170 mmol m2 s-1); nine days after harvest, we had three open-flowers with uniform appearance and catalase activity incremented up to 6.3 Ug-1 fresh weight, whereas the activity of peroxidase was held constant for vase-life (between 0.1 and 0.4 Ug-1 weight). Flowers stored in water showed climacteric behaviour similar to that of the control, lower relative increase in fresh weight, similar water consumption and increased stomatal conductance than the controls; postharvest life went up to 19 days, the enzyme activity of catalase and peroxidase increased, similar to the controls. Dry storage was only feasible for five days.
Keywords: Eustoma grandiflorum; breathing; catalase; sethylene; peroxidase; stomata conductance